Comparative Study of Music and Architecture from the Aesthetic View - Seraj, Seyed Hesamodin (Journal of History Culture and Art Research, 2017)
Beauty is a mental and emotional phenomenon that has a deep connection with the sensory elements around us. Nature is the master key to feel this sense that along with our feelings and emotions, will lead to relative degrees of beauty. Architecture is formed in the material three-dimensional templates and it is more objective than the other arts; In other words, its relations with the material world are more than the other arts; however, music is only capable to form in one dimension and platform namely time and it is freed from the constraints of location. In this way, music art takes shape over time and it is more abstract than painting, and more prominent than architecture, sculpture and painting. Of course architecture, in accordance with this content, has a special connection from the material world to the spiritual world. Especially in Islamic mosques and sacred arts, architecture has a semantic meaning beyond the material world; because in the sacred arts, secrets are pure as it often does not have any outer shapes and they become a symbol of an Islamic belief and a mystical image so that the transformation is performed to adapt an image with religious beliefs. Thus, the research method, according to the examined contents in this study, is based on pure science or library resources and it is as descriptive-analytic. In this paper, some comparative aspects of aesthetics in music and architecture, which has achieved the high degree of beauty in the light of the total shares and coordination between the two arts, are examined as the goals of this transition.